Benefits being created to reduce poverty in our Republic and their effectiveness - Turaboeva Kimiyokhon; Boymurodova Khosiyat Bobokhon qizi (THE INNOVATION ECONOMY, 2026)
The article analyzes the topic of “Poverty Reduction”, which is currently becoming relevant. The measures implemented in our country to reduce poverty, in particular tax and financial incentives, as well as their effectiveness are analyzed.